2022
DOI: 10.1021/acsomega.1c07198
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose Acetate–Cellulose Nanowhisker Nanocomposite Immobilized with a DCDHF-Hydrazone Chromophore toward a Smart Test Strip for Colorimetric Detection of Diethyl Chlorophosphate as a Nerve Agent Mimic

Abstract: Exposure to nerve agents, which are usually colorless and odorless gases, may cause organ failure, paralysis, or even quick death. Diethyl chlorophosphate (DCP) has been recognized as one of the most well-known chemical warfare nerve agent mimics. In the current study, we introduce a simple strategy for the development of a portable and reversible nanocomposite-based microporous strip for naked-eye detection of DCP within a few seconds. A dicyanomethylenedihydrofuran hydrazone (DCDHF-H) chromophore was synthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…L * was highly decreased upon raising the total content of the copper ions to indicate the formation of darker color. a * was increased and switched from negative to positive values representing a colorimetric change from green to red, whereas b * decreased and switched from +b * to −b * to designate a colorimetric change from yellow to blue [32–34] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…L * was highly decreased upon raising the total content of the copper ions to indicate the formation of darker color. a * was increased and switched from negative to positive values representing a colorimetric change from green to red, whereas b * decreased and switched from +b * to −b * to designate a colorimetric change from yellow to blue [32–34] …”
Section: Resultsmentioning
confidence: 99%
“…L* was highly decreased upon raising the total content of the copper ions to indicate the formation of darker color. a* was increased and switched from negative to positive values [32][33][34] Many colorimetric chemosensors have been developed for detection of copper ions, such as Schiff-Bases, [35] pyrenes, [36] chromones, [37] and metal-organic frameworks. [38] However, these chemosensors have shown disadvantages, such as sophisticated and expensive preparation procedures, poor selectivity, lower limit of detection, and difficult to operate under ambient conditions.…”
Section: Colorimetric Study On Paper Dipstickmentioning
confidence: 99%
“…DCDHFH have been used as a halochromic, vapochromic, metallochromic, solvatochromic, biochromic, thermochromic sensing tools. [43,52,53] The UV-Vis absorption spectra of the produced chromophore showed that it has solvatochromic and halochromic capabilities. The introduction of electron-withdrawing groups on the phenylhydrazone group improved the molecular polarizability of the DCDHFH.…”
Section: Thermochromic Mechanism Of Poly (Nipam-co-dcdhfh) Hydrogelmentioning
confidence: 99%
“…The PVA-MFC-H film with the highest content of TCF-hydrazone displayed a weight loss monitored at 495 C. It can be concluded that the immobilization of the organic TCF-hydrazone in the PVA-MFC films results in increasing the rate of pyrolysis. [21,37] It was found that because of the increased weight loss of the QHTCF-immobilized PVA-MFC strips in comparison to the QHTCF-free PVA-MFC strip, their thermal stability was less than that of PVA-MFC. The remaining weight of the PVA-MFC film was controlled to around 18%.…”
Section: Thermal Stabilitymentioning
confidence: 99%
“…There are many methods have been reported to detect nerve agents, including enzymatic, surface acoustic wave, electrochemical, and fluorescent approaches. [20][21][22] These techniques, on the other hand, were sluggish, nonselective, less sensitive, lacking in specificity, and prohibitively costly to use. The usage of electrical and electric components and highly trained employees may also be required.…”
Section: Introductionmentioning
confidence: 99%